RANCANG BANGUN SUPPLY CHAIN MANAGEMENT BUDIDAYA JAMUR BERBASIS WEB (STUDI KASUS: BUDIDAYA JAMUR JATAYUTM) - Ashilla Asyahdina (2021)
In the city of South Tangerang there are mushroom growers who have a high consumer interest. However, in the business process of mushroom cultivation there are obstacles and obstacles. Obstacles that arise is not epressed and stored well recording of mushroom ordering data so that there are often errors in the data collection of mushroom production. From these problems, an improvement is needed to the problem using a Supply Chain Management information system that helps farmers and consumers to provide and get information about mushroom cultivation, and distribute the results of mushroom cultivation to consumers. Supply Chain Management information system is made web-based to more easily access information and can integrate between suppliers, distributors and end consumers. The method in this research uses PIECES analysis method and system development method using Prototyping method. The result of this research is a web-based Supply Chain Management application that is useful for mushroom growers.